Focus Group Discussion mengenai Analisis Pemenuhan Prinsip-Prinsip Penataan Dapil dan Alokasi Kursi dalam Penyelenggaraan Pemilu di Kabupaten Sambas - Akbar, Reza; Asman, Asman; Karman; Syamsiah, Nur; Miswinda (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This Community Service Program (PKM) aims to analyze the fulfillment of the principles of electoral district (dapil) delineation and seat allocation in the administration of the 2024 General Election (Pemilu) in Sambas Regency. Conducted through a collaboration between the General Election Commission (KPU) of Sambas Regency and the Institute for Research and Community Service (LP2M) of Sultan Muhammad Syafiuddin University Sambas, this activity took the form of a Focus Group Discussion (FGD) involving academics, election organizers (KPU and Bawaslu), the Sambas Office of National Unity and Politics (Kesbangpol), and university students. The study was based on seven fundamental principles of electoral district delineation, namely equality of vote value, proportionality, adherence to the proportional electoral system, territorial integrity, coterminous, cohesiveness, and continuity. The results indicate that the seven-district model is more ideal than the five-district model, as it better fulfills the principles of territorial integrity, cohesiveness, and proportional seat allocation, although the five-district model performs better in terms of vote value equality and continuity. Therefore, the delineation of seven electoral districts in Sambas Regency is considered to reflect a more just, democratic, and contextually relevant balance of political representation according to the region’s socio-geographical characteristics.